2005
DOI: 10.21273/hortsci.40.6.1879
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Supplied Nitrogen Form and Quantity on Growth and Postharvest Quality of Ranunculus asiaticus Flowers

Abstract: The form of N supplied to the plant (NH4+ or NO3) affects growth, morphology and a range of physiological processes in the plant. Little information is available concerning the effects of N form on development, production or quality of cut-flowers. The present study investigated for the first time the effects of N form and quantity on growth, flower production and flower quality of Ranunculus asiaticus Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
26
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 26 publications
2
26
0
Order By: Relevance
“…Therefore, if the "stem-topple" disorder in R. asiaticus was related to impaired calcium nutrition, an elevated supply of NH 4 + may exacerbate the severity or extent of the disorder. Nevertheless, we reported that the extent of "stemtopple" in R. asiaticus was not correlated with the level of NH 4 + supplied to the plant (Bernstein et al, 2005). Moreover, the calcium concentrations in leaves from the N-fertilisation treatment that demonstrated significantly lower "stem-topple" damage, were not significantly different from leaves from all other treatments.…”
mentioning
confidence: 73%
See 4 more Smart Citations
“…Therefore, if the "stem-topple" disorder in R. asiaticus was related to impaired calcium nutrition, an elevated supply of NH 4 + may exacerbate the severity or extent of the disorder. Nevertheless, we reported that the extent of "stemtopple" in R. asiaticus was not correlated with the level of NH 4 + supplied to the plant (Bernstein et al, 2005). Moreover, the calcium concentrations in leaves from the N-fertilisation treatment that demonstrated significantly lower "stem-topple" damage, were not significantly different from leaves from all other treatments.…”
mentioning
confidence: 73%
“…Although the overall calcium concentrations in leaves "Stem-topple" in Ranunculus of R. asiaticus were not affected by N-treatment (Bernstein et al, 2005), reduced concentrations of calcium might have been induced locally, in the region of the flower stem sensitive to bending. Such localised alterations in tissue calcium concentrations have been shown to occur in plants, and to affect growth or to induce physiological disorders (Bernstein et al, 1993;1995;Bar-Tal and Pressman, 1996;Ho and Adams, 1989).…”
mentioning
confidence: 88%
See 3 more Smart Citations